Ṭarīqah Mubāsyarah in The Learning of Arabic Speaking Skill: Study Analysis with Al-Iṭṭiṣāli Approach - Ritonga, Nur'ainun; Putra, Wahyu Hanafi; Isnaini, Rohmatun Lukluk (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
This study aims to identify the steps, advantages, and disadvantages of teaching Mahārah Kalām using the Mubāsyarah method with the Iṭṭiṣāli approach. The research employs library research with a qualitative descriptive method. Data collection involves documentation, with primary sources including an article by Baroroh et al., entitled "Arabic Learning Based on a Communicative Approach in Non-Pesantren Schools," and secondary sources being books and scientific articles relevant to the study. Data analysis follows Milles and Huberman's theory, including data reduction, display, and conclusion drawing. The study identifies several steps in Mahārah Kalām learning using the Mubāsyarah method with the Iṭṭiṣāli approach: introduction, presentation of short dialogue formats by teachers, student writing of short dialogues, practice of dialogues, questioning, teacher reading of student dialogues, and evaluation. Advantages of this method include improved speaking skills, expanded vocabulary, pronunciation closer to native speakers, and the ability to analogize with other topics. However, its disadvantages include suitability only for small groups, the need for teachers to speak like natives, reliance on teachers to prepare materials, avoidance of the mother tongue, difficulty in identifying teacher mistakes, and the flawed theoretical basis equating mother tongue acquisition with foreign language learning. The research implies that the Mubāsyarah method is not the sole method for teaching Arabic speaking skills.